9.7k views
5 votes
Multiplying Polynomials and Simplifying Expressions

Multiplying Polynomials and Simplifying Expressions-example-1
User Deuberger
by
4.7k points

1 Answer

2 votes

Given:

Polynomials:
a+3 \text { and }-2 a^(2)+15 a+6 b^(2)

To find:

The product of the polynomials.

Solution:


(a+3)(-2 a^(2)+15 a+6 b^(2))

Using distributive property:
x(y+z)=xy+xz


(a+3)(-2 a^(2)+15 a+6 b^(2))=a(-2 a^(2)+15 a+6 b^(2))+3(-2 a^(2)+15 a+6 b^(2))

Now multiply each of the first term with each of the second term.


=a\left(-2 a^(2)\right)+a \cdot 15 a+a \cdot 6 b^(2)+3\left(-2 a^(2)\right)+3 \cdot 15 a+3 \cdot 6 b^(2)

Applying plus minus rule:
+(-x)=-x


=-2 a^(2) \cdot a+15 a \cdot a+6 a\cdot b^(2)-3 \cdot 2 a^(2)+3 \cdot 15 a+3 \cdot 6 b^(2)

Apply the exponent rule:
x^(n) \cdot x^(m)=x^(n+m)


=-2 a^(3)+15 a^2+6 a b^(2)-6 a^(2)+45 a+18 b^(2)

Add or subtract the like terms:


=-2 a^(3)+15 a^2-6a^2+6 a b^(2)+45 a+18 b^(2)


=-2 a^(3)+9 a^(2)+6 a b^(2)+45 a+18 b^(2)

Arrange in the order.


=-2 a^(3)+9 a^(2)+45 a+6 a b^(2)+18 b^(2)

The product of
a+3 \text { and }-2 a^(2)+15 a+6 b^(2)
-2 a^(3)+9 a^(2)+45 a+6 a b^(2)+18 b^(2).

User GreenOwl
by
4.9k points